Diagnostico y evaluación de la agroindustria arrocera en la región de San Martín - Sólis Macedo, Carlos Alberto (1997)
He present work is on the diagnosis and evaluation of the agro-industry of the rice in the Region san Martin, describes the rice from: varieties sown, conditions of production, systems of sowing and harvest, yields in the field and in them rrolinos, technical in its storage, processing and marketing; both local interregional corro, producing areas, sown areas and production of paddy rice, Park rrolinero, hourly capacity of processing, static capacity of alh'\9cenamiento, category of stores and rrolinos. This work allows you to objectively see what the rice means for our region, where rice is planted in rainfed approximately 2.0 conditions % of production and the ' 98.0% under irrigation system, dominant varieties early and semitardias between the 15.0% and 85.0% respectively. Rrolinero Park represents 60 rrolinos, the hourly capacity of processing 111.5 TM / Ha, alma infrastructure...